Composites of nanodimensional glass in the system Na2O–SiO2/Mesoporous silica and their high ionic conductivity. (July 2020) - Samanta, Subha; Maity, Anupam; Chatterjee, Soumi; Giri, Saurav; Chakravorty, Dipankar
Abstract: Nanodimensional glass samples of compositions x Na2 O-(100– x )SiO2, with x having values of 25, 35, and 45, have been synthesized within the nanochannels of diameter ca. 5 nm of mesoporous silica SBA-15 (Santa Barbara Amorphous 15) by a sol–gel technique. The dc electrical conductivities of the nanocomposites, as well as of bulk glasses, have been determined in the temperature range 300–500 K by carrying out ac impedance measurements over the frequency range 20 Hz to 1 MHz on samples of diameter ca. 10 mm and thickness ca. 0.7 mm, and determining the intersection points of the arcs of circles in the complex impedance plots at high frequency with the real axis. The conductivities of the nanocomposites were found to be 4–5 orders of magnitude higher than those of the corresponding bulk glasses at room temperature. This may be ascribed to the presence of greater free volume in the nanoglasses as compared to their bulk counterparts, thus providing faster pathways for ion migration therein, and hence drastically lowering the activation energy of sodium ion migration. The nanocomposite with 45 mol% Na2 O exhibited an electrical conductivity of the order of 10 −3  S cm −1 at room temperature (ca. 300 K). The nanocomposites also showed outstanding electrochemical performances. The maximum specific capacitance was seen for the nanocomposite with nanoglass composition 45Na2 O–55SiO2, amounting to 1344 F/g at a scan rate of 10 mV/s. Around 88.8% retention of capacitance over 100 successive cycles indicates good sustainability of the samples. These nanocomposites are thus highly promising for the fabrication of solid-state sodium-ion batteries. Highlights: Composites comprising nanoglass in the system Na2 O–SiO2 have been grown within mesoporous silica SBA-15. A facile sol–gel method for synthesizing Na2 O–SiO2 nanoglasses is described. 45Na2 O–55SiO2 /SBA-15 showed high ionic conductivity (ca. 10 −3  S cm −1 ) at 300K, ideally suited for sodium-ion battery system. Such high conductivity is ascribed to the nanoglass configuration at the interfaces, which introduces large free volume.